Analisis Pengaruh Employee Empowerment, Kecerdasan Intelektual dan Komunikasi Interpersonal terhadap Kinerja Aparatur Sipil Negara Melalui Motivasi Kerja dan Kepuasan Kerja - Kiraman Kiraman; Muhtar Sapiri; Wahyu Maulid Adha (Al-Buhuts, 2024)
The aim of this research is to analyze the influence of employee empowerment, intellectual intelligence, interpersonal communication, work motivation and job satisfaction on the performance of State Civil Apparatus, the influence of employee empowerment, intellectual intelligence and interpersonal communication on the performance of State Civil Apparatus through work motivation and job satisfaction at the KPU Office West Sulawesi Province. Data collection techniques through distributing questionnaires with data analysis techniques using Smartpls 3.2.9. The research results found that employee empowerment had a positive and significant influence on ASN performance, intellectual intelligence and interpersonal communication had a negative and insignificant influence on ASN performance, work motivation and job satisfaction had a positive and significant influence on ASN performance. The results of the mediation test show that work motivation can mediate the influence of employee empowerment and intellectual intelligence on ASN performance, work motivation cannot mediate the influence of interpersonal communication on ASN performance. Then job satisfaction can mediate the influence of employee empowerment and intellectual intelligence on ASN performance, while job satisfaction cannot mediate the influence of interpersonal communication on ASN performance at the KPU office of West Sulawesi province.